Infusing creative pedagogy into an English as a foreign language classroom: Learning performance, creativity, and motivation. (September 2018) - Liao, Yu-Hsiu; Chen, Yi-Ling; Chen, Hsueh-Chih; Chang, Yu-Lin
Highlights: Evidence for the effectiveness of creative pedagogy in an ESL classroom with a quasi-experimental approach. Creative pedagogy benefits second language learning. Creative pedagogy improves learning performance, motivation, and creativity. Abstract: This study investigated the impact of creativity pedagogy on learning performance, creativity, and learning motivation in the English as a foreign language (EFL) classroom. With a quasi-experimental approach to assessing treatment effects in the nonequivalent control group design, three instruments of the measure were administered to a sample of 256 elementary school students: 119 and 137 students in the experimental and control groups, respectively. The instruments were an English receptive vocabulary test, the Torrance Test of Creative Thinking, and an English learning motivation questionnaire. The experimental group received an 8-week intervention with regular EFL curriculum-infused activities for creativity. The control group was taught a regular EFL curriculum. The results of one-way analysis of covariance indicated that creativity technique pedagogy significantly improved learners' English learning performance, creativity, and learning motivation. Implications for educators and directions for future research were discussed.